Politische Geographie und Geopolitik.: Bemerkungen zu einem (un-)bestimmbaren Verhältnis - Lossau, Julia (ERDKUNDE, 2002)
If there had been a compulsory directive for German political geographers regarding the current revitalisation of Geopolitik, this directive would have been: Hands off Geopolitik! This remarkable reluctance, which is being overcome only slowly, is even more surprising (if not: unsurprising), as the relationship between political geography and geopolitics has never been clearly defined. Against this background, and in accordance with the deconstructionist/reconstructionist tools of critical geopolitics, this paper seeks to explore this relationship. Exploring, however, does not equal definition, for it will be shown that the links between political geography and geopolitics are both definable and indefinable at the same time. This ambiguity leads to the question of how to react to the increasing usage of geopolitical expressions both inside and outside the discipline of political geography. In the last part of the paper, a strong case is made not for uncritically engaging with but for deconstructing the usage of geopolitical terminology. By drawing this conclusion, the paper gains relevance beyond the realm of German political geography.